Bay Street Theatre
Dinner in honor of renaming the stage of the Bay Street Theatre for Elaine Steinbeck. Foreground: unknown men. Middle ground (from left): unknown woman, Bruce Springsteen, Doctor Susan Shillinglaw, Elaine Steinbeck, Gary Sinise. Background: unknown women and man. The Bay Street Theatre in in Sag Harbor, New York.Original in safe.